A review of the influence of pH on toxicity testing of acidic environmental chemical pollutants in aquatic systems using zebrafish (Danio rerio) and glyphosate toxicity as a case study - Vasisht Varsh Sridhar; Lucas W. Turner; Leeah S. Reidenbach; Katharine A. Horzmann; Jennifer L. Freeman (Ecotoxicology and Environmental Safety)
Glyphosate is an acidic herbicide reported to contaminate water sources around the globe. Glyphosate alters the pH of a solution depending upon the concentration and buffering capacity of the solution in which it is present. Hence, toxicity observed in laboratory-based studies could be caused by the chemical or acidic pH if the solution is not adjusted to neutral conditions, confounding toxicity assessments. When reviewing zebrafish glyphosate toxicity studies, major discrepancies were noted among the published literature. Moreover, it was discovered that most of these studies did not mention pH or neutralization of the test solution. Thirty-six articles were identified when restricting the search from January 2009 through April 2024 to studies testing glyphosate toxicity (as glyphosate or glyphosate-based herbicides) in zebrafish and assessed for time of exposure, test concentrations, and mention or assessment of pH in exposure solutions. Additionally, toxicity curves for unadjusted pH and adjusted pH conditions for glyphosate were also determined in developing zebrafish from 1 to 120 hours post fertilization (hpf), to further clarify and support pH influence of glyphosate in these toxicity tests. Furthermore, a pH toxicity curve was established for the same developmental period to address if the divergence noted in the literature was based on glyphosate’s influence on acidity of the exposure solution. Results showed that at concentrations greater than 10 ppm (mg/L), the pH of the water used in the experiments at chemistry parameters commonly used in zebrafish toxicity studies reduced to 5.5. As the glyphosate concentration increased, the pH continued to drop as low as 2.98. When comparing unneutralized and neutralized glyphosate solutions, the 120 hpf-LC50 without neutralization was close to 50 ppm, while minimal lethality was observed up to 1000 ppm in the neutralized solutions. Findings were then compared to the thirty-six zebrafish glyphosate toxicity studies for alignment of findings with glyphosate or pH toxicity. Eighteen of the studies included treatment concentrations less than 10 ppm with pH likely not to influence reported outcomes. Of the 18 remaining studies at higher concentrations likely to influence pH, only one reported neutralizing their exposure solutions. Two additional studies mentioned pH as a potential driving factor but did not repeat in neutral conditions. As a result, 17 of the 36 studies are observing primarily pH toxicity in the glyphosate assessments. Based on these findings, caution is warranted in interpreting results of acidic environmental contaminants in cases where pH of exposure solutions is not stated.